2004
DOI: 10.1016/j.ympev.2004.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic history of the yellow-necked fieldmouse (Apodemus flavicollis) in Europe and in the Near and Middle East

Abstract: The exact location of glacial refugia and the patterns of postglacial range expansion of European mammals are not yet completely elucidated. Therefore, further detailed studies covering a large part of the Western Palearctic region are still needed. In this order, we sequenced 972 bp of the mitochondrial DNA cytochrome b (mtDNA cyt b) from 124 yellow-necked fieldmice (Apodemus flavicollis) collected from 53 European localities. The aims of the study were to answer the following questions:• Did the Mediterranea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
95
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(118 citation statements)
references
References 36 publications
18
95
0
5
Order By: Relevance
“…Clade II and clade III probably evolved in mild northwestern regions (Black Sea, e.g., Crimea) and southeast of the Caucasus (southern coast of Caspian Sea). These clades are well separated (mean corrected K2P distance: 5.0%), similarly to what was observed in the wild goat (Manceau et al, 1999) and in the yellow-necked Weldmouse (Michaux et al, 2004) in the same region. This event is situated in the Lower Pleistocene, 1.1 Myr BP.…”
Section: Article In Presssupporting
confidence: 77%
See 1 more Smart Citation
“…Clade II and clade III probably evolved in mild northwestern regions (Black Sea, e.g., Crimea) and southeast of the Caucasus (southern coast of Caspian Sea). These clades are well separated (mean corrected K2P distance: 5.0%), similarly to what was observed in the wild goat (Manceau et al, 1999) and in the yellow-necked Weldmouse (Michaux et al, 2004) in the same region. This event is situated in the Lower Pleistocene, 1.1 Myr BP.…”
Section: Article In Presssupporting
confidence: 77%
“…Temperate species, which presently occupy central and northern Europe, mainly derive from Mediterranean refugium populations that underwent range expansion in the late glacial and early post-glacial periods (Hewitt, 1996), with a western form deriving from an Iberian refugium and an eastern form from the Italo-Balkanic refugium (Dumolin-Lapegue et al, 1997;Ferris et al, 1993Ferris et al, , 1998Santucci et al, 1998;Thorpe, 1984). Several authors, however, suggest an additional mode of colonisation of central and northern Europe by non-Mediterranean populations, coming from one or more eastern refugia: Caucasus, southern Ural, central Europe, and western Asia (Bilton et al, 1998;Cooper et al, 1995;Michaux et al, 2004;Nesbo et al, 1999;Palme and Vendramin, 2002;Seddon et al, 2002). A few other species (BrunhoV et al, 2003;Taberlet et al, 1998) …”
Section: Introductionmentioning
confidence: 99%
“…mystacinus comparison (70% of the host and parasite sequences were not sampled in the very same location, but well in locations belonging to the same genetic clade) were responsible for the lack of co-differentiation, we repeated the cospeciation test between Heligmosomoides and A. sylvaticus When the Apodemus host sequences and parasite sequences were not available from the same location, we used instead sequences from close regions which belonged to the same genetic clade, as known from the previously published Apodemus phylogeographies (see Michaux et al, 2003Michaux et al, , 2004Michaux et al, , 2005a. Changes are the followings: a A. sylvaticus sequence comes from Tunisia (Tn).…”
Section: Co-differentiation Analyses Between Heligmosomoides Lineagesmentioning
confidence: 99%
“…Indeed, fossil garden dormouse remains have been found throughout the Middle and Upper Pleistocene in Spain and in southern France (Chaline 1972;Kowalski 2001;Lopez-Garcia et al 2007). In other forest rodents, the Pyrenees did not constitute a biogeographical barrier, either when they moved from the south to north (Apodemus sylvaticus: Michaux et al 2003;Myodes glareolus: Deffontaine et al 2005) or from north to south (Apodemus flavicollis: Michaux et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…The postglacial recolonisation patterns of forest rodents have been extensively studied in recent years (Deffontaine et al 2005;Michaux et al 1998Michaux et al , 2004Nieberding et al 2005). These studies demonstrated that most rodents survived the cold periods of the Quaternary in temperate southern refuges including Spain, Italy and the Balkans.…”
Section: Introductionmentioning
confidence: 99%